Safety and Efficacy of the Noncessation Method of Antithrombotic Agents after Emergency Endoscopic Hemostasis in Patients with Nonvariceal Upper Gastrointestinal Bleeding: A Multicenter Pilot Study. (22nd May 2021) - Yamaguchi, Daisuke; Tominaga, Naoyuki; Miyahara, Koichi; Tsuruoka, Nanae; Sakata, Yasuhisa; Takeuchi, Yuki; Matsunaga, Takuya; Hidaka, Hidenori; Akutagawa, Takashi; Noda, Takahiro; Ogata, Shinichi; Tsunada, Seiji; et al.
Abstract : Background and Aims . The present study aimed to clarify the safety and efficacy of the noncessation method of antithrombotic agents after emergency endoscopic hemostasis in patients with nonvariceal upper gastrointestinal bleeding (UGIB). Methods . In this multicenter, prospective, pilot study, we performed emergency endoscopic hemostasis for nonvariceal UGIB in patients taking antithrombotic agents and resumed the medications without a cessation period (group A). The clinical characteristics, types of antithrombotic agents, UGIB etiology, treatment outcome, and adverse events were evaluated. We used propensity score matching to compare treatment outcomes and adverse events with our previous cohort (group B) in whom antithrombotic agents were transiently discontinued after emergency endoscopic hemostasis. Results . Forty-three consecutive patients were prospectively enrolled. The main antithrombotic agents were low-dose aspirin and direct oral anticoagulants; 11 patients (25.6%) were taking multiple antithrombotics. Peptic ulcers were the main cause of bleeding (95.4%). Endoscopic hemostasis was successful in all patients and the incidence of rebleeding within a month was 7.0%. Propensity score matching created 40 matched pairs. Endoscopic hemostasis was performed by soft coagulation significantly more frequently in group A than in group B (97.5% versus 60.0%, P < 0.001). Neither the rebleeding rate within a month nor thromboembolic event rate was different between the two groups. However, the mean duration of hospitalization was significantly shorter in group A than in group B (8.6 ± 5.2 d versus 14.4 ± 7.1 d, P < 0.001). Conclusions . Antithrombotic agents possibly can be continued after successful emergency endoscopic hemostasis for nonvariceal UGIB.